2021
DOI: 10.3390/min11111244
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Microscopic Analysis of Ferrous Saponite and Its Sensitivity to Oxidation by Earth’s Air: Lessons Learned for Analysis of Returned Samples from Mars and Carbonaceous Asteroids

Abstract: Ferrous saponite is a secondary mineral that can be used to reveal the redox state of past aqueous environments on Mars. In mineralogical analyses for ferrous saponite formed in laboratory simulations or contained in future returned samples from Mars, its oxidation by the Earth’s air could be problematic due to the high redox sensitivity. Here, we performed micro X-ray diffraction and scanning transmission X-ray microscopy analyses for a single particle of synthesized ferrous saponite without any exposure to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…(2021) was shown to accommodate ferric iron while maintaining trioctahedral structure within the 10–18 hr of exposure. The single particle saponites had Fe 3+ /ΣFe of ∼15% and formed ferric iron micro‐vein‐like features after air exposure (Noda et al., 2021). Chemtob et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021) was shown to accommodate ferric iron while maintaining trioctahedral structure within the 10–18 hr of exposure. The single particle saponites had Fe 3+ /ΣFe of ∼15% and formed ferric iron micro‐vein‐like features after air exposure (Noda et al., 2021). Chemtob et al.…”
Section: Discussionmentioning
confidence: 99%
“…Air exposed ferrous saponite by Noda et al (2021) was shown to accommodate ferric iron while maintaining trioctahedral structure within the 10-18 hr of exposure. The single particle saponites had Fe 3+ /ΣFe of ∼15% and formed ferric iron micro-vein-like features after air exposure (Noda et al, 2021). Chemtob et al (2017) found XRD hematite peaks after hydrothermally recrystallizing H 2 O 2 oxidized, Fe 2+ -rich smectites; they concluded that the hematite represented the recrystallization product of poorly crystalline Fe oxyhydroxides formed by iron ejection during oxidation.…”
Section: Structural and Mineralogical Changes With Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nontronite (NDJB26), saponite (LASA53), and Fe-bearing saponite (LASA59) are obtained from the Reflectance Experiment Laboratory (RELAB) spectral library, which is regularly updated by the CRISM team in the CAT ENVI tool (Morgan et al 2017, and references therein). Fe-bearing saponites (e.g., Griffith saponite or Griffithite) have been suggested for clays detected at Yellowknife Bay in Gale crater and elsewhere on Mars (e.g., Treiman et al 2014;Chemtob et al 2015;Fox et al 2021;Noda et al 2021); they have characteristic absorptions near 1.40-1.42 μm, 2.30-2.32 μm, and 2.40 μm. Pure vermiculite (GDS469L) and hydrobiotite (GDS469M) are handpicked ground flakes of a sample collected near Libby, Montana (Swayze et al 2018).…”
Section: Clay Mineralogymentioning
confidence: 99%
“…Besides the noise and dust cover, the lack of absorption near 2.4 μm could be due to compositional properties of Fe-saponites and pure vermiculites, the two possible candidate minerals. Fe-rich saponites have a very weak overtone near 2.4 μm, only recognizable after continuum removal (Figure 4(c); see, e.g., Treiman et al 2014;Chemtob et al 2015;Fox et al 2021;Noda et al 2021). Although the large variety of spectra for vermiculite ores implies diverse band depths and centers in the near-infrared spectral range (e.g., Swayze et al 2018;Krzesińska et al 2021;Cuadros et al 2022), pure vermiculite also has a 2.4 μm absorption relatively weaker than in hydrobiotite and other clay minerals (saponites and nontronites; Figure 4(c)).…”
Section: Clay Mineralogymentioning
confidence: 99%